Determination of Healthy Lifestyle Patterns and Physical Activity in Improving Physical Fitness - Siska Aprelyani (Siber International Journal of Sport Education, 2025)
Literature Review Determination of Healthy Lifestyle Patterns and Physical Activity in Improving Physical Fitness is a scientific article with the aim of analyzing whether physical fitness plays a role in healthy lifestyle patterns and physical activity. The method examines various studies, articles, and books that are relevant to the topic discussed. The results of this article are: 1) Healthy Lifestyle Patterns play a role in Physical Fitness; 2) Physical Activity plays a role in Physical Fitness. Apart from these 2 exogenous variables that affect the endogenous variable of Physical Fitness, there are still many other factors including health, sports, physical exercise.